Socio-economic factors for the educational inequality in China - Wu, Jiaxi (2024)
This thesis examines the socio-economic factors contributing to educational inequality in China, focusing on the period from 2010 to 2022. Despite education being a fundamental human right, disparities in access and outcomes persist across rural-urban divides, regions, and social groups. The paper analyzes the relationship between educational inequality and economic development, exploring the roles of gender, income inequality, and rural-urban differences. Based on classical theories for labor as a production factor from 19th and early 20th century, it argues that educational inequality hinders economic opportunities, particularly for disadvantaged groups, affecting national economic growth. Using the Gini coefficient decomposition method with data from the Chinese General Social Survey, the findings show that rural-urban and income disparities drive educational inequality. The paper concludes with policy recommendations, including increased investment in rural education, gender equality, and social welfare for disadvantaged groups, to foster a more equitable education system and promote economic growth.